Cadar dan Aturan Berpakaian Dalam Perspektif Syariat Islam - ., Hasiah (IAIN Padangsidimpuan, 2019)
The purpose of this study are: 1) Knowing the nature of the veil, 2) Knowing the history of the emergence of veils in the culture of Islamic society, 3) Knowing the perspective of Islamic law on the use of veils. This type of research is a literature study (Library Research), the object in this study is the concept of veil in the perspective of sharia based on the Qur'an and hadith, the veil controversy in the culture of society. Data is collected by quoting, analyzing using the legal and historical approach methods that occur regarding the use of veils in people's lives.So the veil is a part of sharia after Islam came which was brought by the Prophet Muhammad. And it is also a culture that has occurred for generations before the existence of Islam (jahiliyah period).